Implementation Of The Principle Of Systematic Specification To Criminal Laws In Criminal Cases Of Corruption - Dhoni - Martien (Faculty of Law, Universitas Pekalongan, 2022)
This study aims to identify and analyze the application of the principle of systematic specificity in customs criminal law in corruption cases. The research method used is empirical research with case studies through a statutory approach. The results of the research show that the reformulation of the principle of systematic specificity in customs crimes is a derivative of the principle of lex specialis derogate legi generali. The principle of systematic specificity needs to be reformulated by adding paragraph 3 to the provisions of Article 63 of the Criminal Code so that the position, parameters and concept are clear so that it does not cause multiple interpretations. The principle of conditional systematic specificity needs to be studied as a personal subject, the object of the alleged act that was violated, the evidence obtained, as well as the environment and the area of offense before law enforcement